A Safe Space Amid Debt: Social and Cultural Practices in In-donesia's Digital Community of Online Loan Default Survi-vors - Gusti Louisa; Augustin Mustika Chairil (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This article examines how a group of people sharing the experience of online loan default builds its own social and cultural order in digital space, using the Facebook group